α-Taxilin Interacts with Sorting Nexin 4 and Participates in the Recycling Pathway of Transferrin Receptor - Sakane, Hiroshi (Public Library of Science, 2014)
Membrane traffic plays a crucial role in delivering proteins and lipids to their intracellular destinations. We previously identified α-taxilin as a binding partner of the syntaxin family, which is involved in intracellular vesicle traffic. α-Taxilin is overexpressed in tumor tissues and interacts with polymerized tubulin, but the precise function of α-taxilin remains unclear. Receptor proteins on the plasma membrane are internalized, delivered to early endosomes and then either sorted to the lysosome for degradation or recycled back to the plasma membrane. In this study, we found that knockdown of α-taxilin induced the lysosomal degradation of transferrin receptor (TfnR), a well-known receptor which is generally recycled back to the plasma membrane after internalization, and impeded the recycling of transferrin. α-Taxilin was immunoprecipitated with sorting nexin 4 (SNX4), which is involved in the recycling of TfnR. Furthermore, knockdown of α-taxilin decreased the number and length of SNX4-positive tubular structures. We report for the first time that α-taxilin interacts with SNX4 and plays a role in the recycling pathway of TfnR.